2019
DOI: 10.4314/nvj.v39i4.9
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasites of bile and faeces of slaughtered cattle and sheep from Maiduguri Municipal Abattoir, North Eastern Nigeria

Abstract: The occurrence and types of gastrointestinal parasites of bile and faeces of cattle and sheep from the semi-arid region of Maiduguri, North-Eastern Nigeria were determined using standard parasitological techniques. Samples of bile and faeces collected from three hundred and eighty seven (387) cattle and 389 sheep were analysed using bile sedimentation, faecal sedimentation and faecal floatation. An overall prevalence of 42.63% was found in cattle, while 49.36% was in sheep. Results from both species did not va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
1
0
0
Order By: Relevance
“…This agreed with Usman et al, 2016 The result in this study also indicated that, the adult animals have higher prevalence rate when compared with young. This agreed with previous report of Jegede et al (2015) and Luka et al (2018) but contrary with other studies which show that adult and old animals develop acquired immunity against helminthic infections as they get mature due to repeated exposure and this will help expel the parasite before it establish itself in the gastrointestinal Tract (Taswar et al, 2010;Dagnachew et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…This agreed with Usman et al, 2016 The result in this study also indicated that, the adult animals have higher prevalence rate when compared with young. This agreed with previous report of Jegede et al (2015) and Luka et al (2018) but contrary with other studies which show that adult and old animals develop acquired immunity against helminthic infections as they get mature due to repeated exposure and this will help expel the parasite before it establish itself in the gastrointestinal Tract (Taswar et al, 2010;Dagnachew et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Gastrointestinal parasites are parasites that inhabit the gastrointestinal (digestive) tract. They include protozoans, helminths and nematodes [6][7][8] . In ruminants, results in adverse effects on feed intake, growth rate, carcass weight and composition, wool growth, fertility and milk yield 9 .…”
Section: Introductionmentioning
confidence: 99%